Fabrication and characterization of carbon nanotube intermolecular p–n junctions - Li, H. (2013)
We demonstrate carbon nanotube intermolecular p–n junctions and study the electron transport mechanisms. Thermionic emission is the main transport mechanisms under forward bias while tunneling dominates the electron transport of the reverse bias condition. A kink point appearing on the plot of ln(I/V2) versus 1/V indicates that the transport mechanism experiences a transition from direct tunneling to the Fowler–Nordheim tunneling under the reverse bias condition. In contrast, the Arrhenius plot of the I–V curve at forward biases suggests that tunneling is more important than the thermionic emission below 50 K.